THE TRANSFORMATION OF BADUY LEARNING CULTURE IN BANTEN - Sutoto Sutoto (Jurnal Pendidikan dan Pengajaran, 2017)
The research objective to acknowledge about meaning of transformation in the management of Baduy tribe learning culture which until now apply customary law of school prohibition. Research using ethnography methodology with some techniques, such as observation, interview, and document review. The data were analyzed by Spradley technique consisting of domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. The research sources were tribe leaders, village leaders, educators, parents, and students. Based on qualitative data analysis, the result research has concluded that negotiation is needed to change the organizational environment and develop human resources, but customary school restrictions should not be changed. Transformational leaders apply the following learning culture control systems with close management registration, learning or schooling secretly, and educational activities centered on the borders of Ulayat lands. Thus conditions could be accepted by tribe leaders.